Aging in German industries and selected professions - Golo Henseke; Pascal Hetze; Thusnelda Tivig (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
Population aging translates into aging of the labor force. However, the impact of the former on the latter is neither straightforward nor uniform over specific groups. The reason is that economic decisions concerning, for example, duration of schooling or labor-market participation of women and those aged 60+ as well as industry-specific requirements on the demand side affect age-specific employment rates and thus the age structure of labor. In this paper we describe and use different measures of aging to obtain a picture of the aging process in selected German industries and professions between 1980 and 2000. Our results reveal pronounced differences in the age structure, timing and dynamics of aging. However, we find that aging is, in general, subject to convergence towards a homogenous age composition: Subgroups that were relatively young in 1980 aged faster, and vice versa.
Keywords: J21; J11; J01; 330; Industriearbeiter; Beruf; Alternde Bevölkerung; Ältere Arbeitskräfte; Deutschland